Implementation of Reel as American Popular Culture for Improving Speaking Media - Bestari, Ade Christanty Yudha; Faiza, Dinar; Mayekti, Meilina Haris; Dodiyanto, Rosyid (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2024)
This research contains an analysis of the implementation of reels on Instagram as American Popular Culture as a medium for improving speaking. The purpose of this research is to determine the implementation process and impact of implementing reels on Instagram as American Popular Culture as a medium for improving speaking. This research uses a qualitative approach using the interview method. The sampling technique was carried out by purposive sampling of students in the Speaking course. This research presents student perceptions about the implementation process and content as well as the impact of implementation. The results of this research, first are the process and content of implementing reels in learning. Second, the impact of implementing the reel is (a) expression and confidence in speaking (b) grammatical understanding in speaking (c) increasing pronunciation (d) vocabulary improvement.